FBXW2 suppresses proliferation and invasion of lung cancer cells by targeting SKP2 and β-catenin. (4th July 2019) - Yang, Fei; Sun, Yi
ABSTRACT: F-box protein is a substrate-receptor of SKP1-Cullin1-F-box protein (SCF) E3 ligase, but the function of many family members remains elusive. We found that F-box and WD-repeat domain-containing 2 (FBXW2) inhibits proliferation and invasion of lung cancer cells by targeting S phase kinase-associated protein 2 (SKP2) and β-catenin for degradation. Lower FBXW2 predicts a worse patient survival. Thus, FBXW2 appears a lung tumor suppressor.